Identification of the Main Water Quality Parameters for Monitoring and Evaluating Watershed Health - Pranatasari Dyah Susanti; Nining Wahyuningrum (Faculty of Geography, Universitas Gadjah Mada, 2020)
Water quality is one of the crucial parameters in monitoring and evaluating watersheds. A large number of parameters causes the monitoring and evaluation of watershed performance to be less efficient and costly. This study aims to determine the main parameters as a method of simplifying water quality observation parameters by producing equations that can be used to predict the level of pollution of a non-point source pollutant (watershed). A sampling of surface water was carried out by purposive sampling at several outlets located in the Brantas and Upper Solo watersheds. The research parameters analysed were: TSS, TDS, BOD, COD, Phenol, Free Chlorineine, Sulfide, Arsenic, Fe, Pb, Phosphate, Nitrate, Nitrite, Detergent, Turbidity and E. Coli. The results of the analysis of water quality are used to calculate the value of the Pollution Index (PI) according to the Decree of the Minister of Environment No. 115 of 2003 and to determine the class of water quality standards that refer to Class III water quality standards, in Government Regulation No.82 of 2001. The analysis showed that all samples were at mild to moderate pollution levels, and did not meet class III water quality standards. Multiple regression analysis produced two equations, namely: Model 1: PI = 3.952 + 91.668 Phenol and Model 2: PI = 3.086 + 80.167 Phenol + 0.152 BOD, with R squared values of 53% and 69.9% with a confidence level of 0.005. Thus the prediction of pollution levels of similar watershed can be made only by using the two most influential parameters namely phenol and/or BOD alone.